Using Technology for the Competitive Delivery of Education Services - Hosie, Peter; Mazzarol, T. (Blackwell Science Ltd, 1999)
This paper considers the use of information technology as a source of competitive advantage for education service providers operating in international markets, with particular reference to Australia. It draws upon the findings of a survey of 315 education institutions in five countries engaged in the export of international education. The importance of effective use of information technology as a source of competitive advantage is highlighted. Current use of information technology within education institutions is examined and technologically mediated learning is proposed as a viable means of promoting, administering and delivering education services to international markets. In particular, the potential of the Internet to provide graduate business education is given close scrutiny. It is argued that a virtual university business faculty is economically viable in this context. Business schools are advised to invest in hardware and software applications to ensure the communications needs of their clients are met.